2020
DOI: 10.1519/jsc.0000000000003529
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Changes in Neuromuscular Responses During the Performance of Leg Extension Repetitions to Failure Below and Above Critical Resistance in Women

Abstract: Dinyer, TK, Byrd, MT, Succi, PJ, and Bergstrom, HC. The time course of changes in neuromuscular responses during the performance of leg extension repetitions to failure below and above critical resistance in women. J Strength Cond Res 36(3): 608-614, 2022-Critical resistance (CR) is the highest sustainable resistance that can be completed for an extended number of repetitions. Exercise performed below (CR 215% ) and above (CR +15% ) CR may represent 2 distinct intensities that demonstrate separate mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…These findings are reinforced by non-invasive 31 P-magnetic resonance spectroscopy assessment of the skeletal muscle metabolic responses, which demonstrate striking differences in the profiles of PCr, inorganic phosphate and pH for exercise performed just above, compared to just below, CP (Jones et al 2008 ). These differences in the rates of substrate utilisation and metabolite accumulation likely underpin observations that the rate and nature of neuromuscular fatigue development also differ according to the intensity of the exercise task relative to CP (Black et al 2017 ; Burnley et al 2012 ; Dinyer et al 2020 ; Pethick et al 2020 ). Finally, it is pertinent to note that simultaneous assessment of the responses of muscle [lactate] and blood [lactate] during heavy-intensity and severe-intensity exercise reveal that the former may be stable while the latter rises (Jones et al 2019b ), suggesting differences in the dynamics of lactate accumulation in the muscle and blood compartments.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are reinforced by non-invasive 31 P-magnetic resonance spectroscopy assessment of the skeletal muscle metabolic responses, which demonstrate striking differences in the profiles of PCr, inorganic phosphate and pH for exercise performed just above, compared to just below, CP (Jones et al 2008 ). These differences in the rates of substrate utilisation and metabolite accumulation likely underpin observations that the rate and nature of neuromuscular fatigue development also differ according to the intensity of the exercise task relative to CP (Black et al 2017 ; Burnley et al 2012 ; Dinyer et al 2020 ; Pethick et al 2020 ). Finally, it is pertinent to note that simultaneous assessment of the responses of muscle [lactate] and blood [lactate] during heavy-intensity and severe-intensity exercise reveal that the former may be stable while the latter rises (Jones et al 2019b ), suggesting differences in the dynamics of lactate accumulation in the muscle and blood compartments.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the load selection, the cadence of the repetitions to failure is an important consideration in the modeling of DCER exercise. At this time, investigators [34][35][36][37][38] have controlled the cadence in the initial applications of the model. The specific cadence has varied across exercises, from 1.1 to 1.5 s per contraction phase (i.e., concentric and eccentric), depending on the specific nature of the movement.…”
Section: Additional Methodological Considerations For the Determination Of The CL Test Parametersmentioning
confidence: 99%
“…The original work of Monod and Scherrer [6] and Moritani et al [7] led to the application of the CP concept to other modes of exercise, including running [13], swimming [32], and rowing [33], such that a linear relationship can be derived from the total work completed and time to exhaustion for each different modality. It is this body of work over the last 50 plus years that has expanded our understanding of the limits of human performance and led to the recent application of the CP model to DCER exercises, including the bench press [34], leg press [35], deadlift [36], and leg extension [37]. The same hyperbolic relationship that has been established across various continuous, whole-body, dynamic movements has also been demonstrated for upper-, lower-, and whole-body DCER exercises (Figure 3).…”
Section: Progression Of the Modeling Across Exercise Modalities: Applications Of The Critical Power Model To Dcer Exercisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, investigators have reported increases in EMG and MMG AMP and decreases in EMG and MMG MPF over time during fatiguing isokinetic, isometric, and dynamic constant external resistance (DCER) muscle actions. 5,6,7,8 These responses indicate there are increases in muscle excitation and motor unit recruitment and decreases in the motor unit action potential conduction velocity and the motor unit firing rate to maintain force production during the fatiguing task.…”
Section: Introductionmentioning
confidence: 99%